From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Knowledge Positions in Aotearoa and Turtle Island Art Museums - Eshraghi, Leuli; Ash-Milby, Kathleen; Nuku, Maia; Borell, Nigel (Artlink, 2020)
Art, performance, and spoken or now written text, all belong to the same register of cultural practice in the First Nations I am familiar with or belong to: ceremony. This ceremonial register takes place in a set of spaces created to enact cultural responsibilities to place, people and balance. Galleries and museums, as sites of cultural production and presentation, have the potential to nurture new ceremonies and new working methods.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonize Me - Igloliorte, Heather; Loft, Steve; Croft, Brenda L. (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2012)
Catalogue d'exposition avec des textes de Loft, Igloliorte et Croft. Galerie d'art d'Ottawa.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Indigenous and decolonizing studies in education, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.--publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Racial Logics, Franchising, and Video Game Genres: The Lord of the Rings - Young, Helen (Games and Culture, 2016)
This article explores the ways game adaptations engage with existing popular culture constructions of race within the framework of commercial franchises. Its focus is on games which are part of the so-called “Frodo Franchise” based on Peter Jackson’s Lord of the Rings and The Hobbit films. It considers the role played by licensing agreements, the conventions, and ludic elements of different game genres, the need for new characters and narratives to keep audiences engaged with an existing world, and the opportunity games offer for interactive exploration of a digital world, to illuminate both the challenges to and the opportunities for disrupting conventional representations of race and difference.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé

The Current State of Muslim Representation in Video Games - Khan, Imad; Khalaf, Farah; Ismail, Rami; Ramzan, Romana (2016)
Muslim members of the video game industry discuss the current state of Muslim representation within video games. This includes current problems with the way Muslims are represented and potential solutions. Our panelists come from all sides of the industry. From AAA, to indie, the panelists all have a unique voice and angle they would like to bring to the discussion. All panelists have grown up Muslim in western countries and have had to deal with certain adversities and challenges. It's through that experience that the panelists want to bring a lively discussion, backed with personal accounts and sources, that is not only engaging, but educational.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public : art, culture, ideas, 0845-4450 ; volume 27, issue 54, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonizing Methodologies: Research and Indigenous Peoples - Tuhiwai Smith, Linda (Zed books, 2012)
To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory. This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being. Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé